DIMENSIONAL RIDGE ALTERATIONS AND HISTOMORPHOMETRIC ANALYSIS FOLLOWING SOCKET PRESERVATION WITH PRF OR ALLOGRAFT. RANDOMIZED CONTROLLED CLINICAL STUDY - Vasilena Ivanova; Ivan Chenchev; Stefan Zlatev; Nikolay Kanazirski (Peytchinski Publishing, 2019)
Purpose: The aim of this randomized controlled clinical trial was to evaluate the efficacy of A-PRF alone or in combination with freeze-dried bone allograft in improving vital bone formation and decreasing alveolar bone resorption. Materials and methods: The study included 60 patients with 63 post-extraction sockets. They were divided into three groups - socket preservation with freeze-dried bone allograft (BoneAlbumin™, OrthoSera Dental, Gyor, Hungary), which consisted of 28 patients. The second group presented post-extraction sockets filled with PRF as a sole grafting material - 23 patients and the third group was the control group - 12 patients. Two scans with Trios intraoral scanner were performed on each patient - one during the socket preservation procedure and one 4 months after. The changes of alveolar height and width were assessed on the superimposed virtual models obtained from the intraoral scanner. Bone biopsy was harvested from the preserved area with a trephine drill 4 months after the extraction. Results: Results reveal that vertical and horizontal bone resorption were less pronounced in both of the tested groups as opposed in the control group, where these values were significantly higher. There was a significant difference between the quantity of the newly formed bone in the control group and both of the tested groups - PRF and allograft. Conclusions: The study reveals that A-PRF as a sole grafting material or FDBA in combination with PRF membrane are both suitable for ridge preservation procedures. The study demonstrates a novel in vivo method for measuring bone resorption after ridge augmentation procedures.